Hematopoietic Chimera in a Male Blood Donor and His Dizygotic Twin Sister - Miola, Marcos P.; Lopes, Alessandro G. [UNESP]; Silva, Alessandra P.; Gomes, Edney G. C.; Machado, Leticia A. F.; Veloso, Wanessa A.; Costa, Carlos A.; Fachini, Roberta M.; Ricci Junior, Octavio; Brandao de Mattos, Cinara C.; Mattos, Luiz Carlos de (Karger, 2019)
Twin hematopoietic chimera in humans is a phenomenon that was discovered accidentally and the prevalence of which remains unclear. The resolution of chimera cases requires studying family medical records, data analysis, and investigations of hematopoietic cells and cells from other tissues. The interactions among ABO, Lewis, and secretor histo-blood group systems are explored to resolve cases of hematopoietic chimera. Here we report a rare case of hematopoietic chimera where twins present a mixed field reaction in the ABO, Rh, and Kidd red blood cell phenotyping. Using red blood cells separated from the mixed field as well as molecular approaches and investigations of family members, we identify inconsistent genotypes with the Mendelian inheritance pattern when comparing the peripheral blood with the buccal epithelium of the male twin and his twin sister. Analysis of the ABO, Lewis, and secretor phenotypes, and genomic DNA from buccal epithelium showed the genotypes ABO*A1.01/ABO*B.01 and FUT2*01N.02/FUT2*01N.02 in the male twin and the genotypes ABO*O.01.01/ABO*O.01.02 and FUT2*01/FUT2*01 in the female twin. The results of the HLA-DRB1 genotyping showed inconsistency between the male and his twin sister. We conclude that the serological analyses combined with molecular approaches used in this study are good tools to resolve cases of hematopoietic chimera. (C) 2019 S. Karger AG, Basel
Keywords: Chimerism; Dizygotic twins; Blood groups; Phenotyping; Molecular analysis